Intelligent Course Timetable Scheduling Using Memetics (International Journal of Engineering and Computer Science, 2017)
A college timetable is a temporal arrangement of a set of lectures and classroomsin which all given constraints are satisfied. Hence, timetabling problem is one of the best examples of a Constraint Satisfaction Problem (CSP). Memetic Algorithm is one of the best techniques to solve the Constraint Satisfaction Problem(CSP) and it is a combination of standard genetic algorithm and hill climbing algorithm. In this paper Course Timetable Scheduling System (CTSS) is developed to solve Timetabling – Constraint Satisfaction Problemwhich makes use of Memetic algorithm.